Cartographies of care: Ecologic thinking-with the bio-geo-microscopic life of the West Antarctic - King , Louisa; Salehian , Tamsin (Interstices: Journal of Architecture and Related Arts, 2022)
“Remote care through the cartographic reach” proposes deep-time thinking and ecological listening as methods for engaging with Antarctic geographies. The architecture of remote landscapes requires considering a more-than-human approach to relational practices to rebuild what Donna Haraway calls the “quiet places,” the places left over in the ruination of late climate change. With mutating earth systems and ecological collapse, “quiet places” are often far away, fragile, and fictional in our imagination. But connecting with these places is to access the more intricate stories of climate change and offer alternatives to the binary fixtures of apocalyptic climate narratives. This paper follows an affectual reading of the material of the traditional cartographic approach, mapping microscopic terraforming endoliths and extremophile mosses of the West Antarctic Dry Valleys. Reorienting mapping towards worlding practices follows the vital flows of matter that enact the agenda of cartography through a lens of radical care.